PENGARUH KUALITAS WEBSITE DAN ONLINE CUSTOMER REVIEW TERHADAP MINAT BELI ULANG PELANGGAN BLIBLI DI SURABAYA - Naufal Putra Yundra Perkasa; Nuruni Ika Kusuma Wardhani (STKIP Persada Khatulistiwa Sintang, 2023)
Customers who wish to shop online must visit the website and see product reviews before making a decision, therefore the quality of the website and user reviews are crucial factors. This research was conducted with the aim of knowing the effect of website quality as well as online customer reviews on customer repurchase intentions on the Blibli marketplace. This study uses a sample size of 72 people who have shopped or are currently shopping on the Blibli website. For this study, information retrieval used a questionnaire distribution method in the southern part of Surabaya. The variables in this study that were chosen by the researcher were Website Quality (X1) and Online customer reviews (X2) as independent variables and then Repurchase Intention (Y) as the dependent variable. for this study using the analysis model that is PLS, as well as for sampling used is nonprobability sampling and the technique for analysis using purposive sampling is a technique using various considerations to determine the study sample. The results of this study show that good website quality and positive online customer reviews can encourage customer repurchase interest in the Blibli marketplace